Determination of Journalism and Communication Transformation under the Disruption of Digital Technology in Thailand during 21st Century - Intaratat , Kamolrat (Research Developments in Arts and Social Studies Vol. 4, 2022)
“The present study aims to determine the cur-rent situation relevant to competency development in Journalism & Commu- nication in Thailand as well as future demands relevant to competency de- velopment in Journalism & Communication in Thailand. Thailand’s vision “Thailand becomes a developed country with security, pros- perity and sustainability in accordance with the sufficiency economy philoso- phy” is the country’s vision stipulated in the national strategy, which can be re- ferred to in short as the national motto of “security, prosperity and sustainability”. Mix methods are quantitative research with e-questionnaire among 48 academia and qualita- tive researches by Focus Group Discussion among 10 stakeholders from all levels. Descriptive statistics and narration were used for data analysis. The overall findings found that the functions of journalists and communicators acquiring the qualities of digital multimedia, digital multi-tasking, or mastering with digital media capacity such as working with information via modern digital technologies aligned with the current demands of this digital disruption era. Thus, journalism and communication education in this digital era must be integrated designed agilely among all sectors in the digital technology ecology: humanism, digital tech- nology and media with its well fit designed by all appropriated educational pedagogies.